THE SINKING OF FOREIGN FISHING VESSELS THAT COMMIT ILLEGAL FISHING IN INDONESIAN SEA TERRITORY IN REVIEW OF THE 2012 MEMORANDUM OF UNDERSTANDING - Shely, Shely; Imelda Cornelis, Vieta; Marwiyah, Siti; Widodo, Ernu (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Indonesia has a vast territory, most of which consists of the sea. Indonesia's strength lies in its natural resources, particularly the abundant marine resources, especially in incredibly diverse fisheries. With the many benefits received by the Indonesian nation, it also brings issues such as limited surveillance capabilities at sea and Indonesia's strategically located territory that can provide opportunities for the exploitation of marine resources by irresponsible parties, particularly the most frequent criminal activity, which is illegal fishing by foreign parties, resulting in significant losses for the country. The problem statement encompasses two aspects for examination: firstly, whether Indonesia's act of sinking Malaysian-flagged vessels can be justified based on the 2012 Memorandum of Understanding between Indonesia and Malaysia; secondly, the legal efforts Indonesia must undertake to defend its territorial sovereignty from illegal fishing activities by foreign fishing vessels. The research method used was normative legal research, examining from the perspective of positive law. The research findings reveal discrepancies in Indonesia's actions of sinking Malaysian-flagged vessels based on the 2012 Memorandum of Understanding. Consequently, Indonesia has fulfilled its obligations as stipulated in the Fisheries Law. However, this fulfillment of obligations occurred without prior investigation into the previously agreed bilateral agreements.